“A Production Center”: A Model of Creative Work in Tadeusz Konwicki’s Early Prose - Miernecka, Martyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The aim of this article is to outline the issues related to the specificity of the image of the writer and his role in society created in Tadeusz Konwicki’s early works. This stage in the writer’s life opens with the first short story that Konwicki published, namely “Kapral Koziołek i ja” from 1947, after which the initial model of his writing is subject to gradual erosion and ends between 1954 and 1955 with the novel titled Z oblężonego miasta. Investigating the motif of the creative work house on the basis of Z oblężonego miasta is a pretext for reflection on the category of the writer’s work. The article traces the motifs of the professional category of the writer, through analysing the constructions on which Konwicki’s narratives are based. At the same time, due to the analysis of social discourse in which the author participated, the article outlines the social functions he performed at a given time.